Big Picard theorem for meromorphic mappings with moving hyperplanes in Pn(C) - Quang, Si Duc; Giang, Ha Huong (Український математичний журнал, 2014)
We present some extension theorems in the style of the Big Picard theorem for meromorphic mappings of Cm into Pn(C) with a few moving hyperplanes.